Incorporating crime in household surveys: a research note - Garrett, James L.; Ahmed, Akhter (SAGE Publications, 2004)
This paper discusses how to incorporate questions about crime into household surveys, drawing on the authors’ experience of designing and implementing a module on crime, violence and physical insecurity in a household survey in the city of Dinajpur in Bangladesh in 2002. The paper discusses issues of design, such as determining survey objectives and the questions that follow from these, involving knowledgeable local partners, determining sample size and designing the questionnaire (and the role of consultations and focus group discussions as well as pre-testing). Then it reports on the findings which highlight the multifaceted nature of crime, the number of people affected (one in six interviewees had been a victim of crime in the 12 months preceding the interview), the role of mastaans (local strong-men) in crime, people’s lack of confidence in the police and the legal system (in part because of the lack of official action against perpetrators), and crime’s direct and indirect costs.